PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAMPANDANGAN ISLAM - Budi Gautama Siregar (Institut Agama Islam Negeri Batusangkar, 2016)
Corporate Social Responsibility (CSR) is basically the moral responsibility of companies and enterprises toward societies. The responsibility itself can be initiated by the company itself, employees, other companies, social environments, and even the State where the business is established. The concept of CSR can be seen from two different perspectives. First, it concerns with the company’s goal is for profit. Therefore, CSR is believed to be parts of business. Second, it deals with the purpose of a company is for profit while ensuring people’s welfare and environmental sustainability become prior concerns. Islam strongly supports CSR since it cannot be denied that the businesses create a lot of unexpected social problems. Consequently, it is the companies and enterprises’ responsibility to fix those problems. This is reasonable since they need to explore a variety of natural resources for business sustainability, therefore, they should be responsible for the people and environment in return.Kata kunci: implementasi, tanggung jawab sosial perusahaan, pandangan Islam